2015
DOI: 10.2147/tcrm.s86226
|View full text |Cite
|
Sign up to set email alerts
|

National consumption of opioid and nonopioid analgesics in Croatia: 2007–2013

Abstract: BackgroundThe increased consumption of analgesics has been documented worldwide during the last 2 decades. The aim of the study was to examine the trends in opioid and nonopioid analgesic consumption in Croatia between 2007 and 2013.MethodsData on opioid consumption were extracted from the database of the national authority. All opioid and nonopioid analgesics were included in the analysis. Data were presented as defined daily doses per 1,000 inhabitants per day. Adequacy of opioid consumption was calculated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Increasing consumption of analgesics in Croatia has been recently reported, 26 but our study also points out that there are still deficiencies in pain treatment following surgery. Even though there is evidence that prescribing patterns are changing, 27 there is still plenty to be done in the field of postoperative pain management.…”
Section: Discussionsupporting
confidence: 59%
“…Increasing consumption of analgesics in Croatia has been recently reported, 26 but our study also points out that there are still deficiencies in pain treatment following surgery. Even though there is evidence that prescribing patterns are changing, 27 there is still plenty to be done in the field of postoperative pain management.…”
Section: Discussionsupporting
confidence: 59%
“…Among a plethora of treatments, opioid agonists are one pharmacotherapy for moderate-severe pain. Although its consumption by country (mg/capita) has increased in the last two decades [ 2 , 3 , 4 ], it may remain under-requirements for managing moderate-severe pain in some regions, including Asian countries [ 1 , 4 , 5 ]. According to the 2015 opioid consumption data, the medical opioid consumption in the United States (U.S.) was 678 mg/capita while in South Korea (S. Korea), it was 55 mg/capita which was below average, ranking 43rd globally and 30th among thirty-five Organisation for Economic Cooperation and Development (OECD) countries (258 mg/capita average in OECD countries) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Opioid consumption level in Spain, Italy, Greece, and Croatia was significantly lower than in Germany, Austria, Belgium, and Denmark ( 22 – 24 ). Our previous investigation showed that the total opioid analgesic consumption in Serbia, in 2012 and 2013, was 8.83 and 8.55 times lower than in Croatia, respectively ( 25 ).…”
Section: Discussionmentioning
confidence: 88%
“…However, European countries themselves had different trends in the opioid utilization. Study performed from 2002 to 2006 showed increased consumption of opioids in all Scandinavian countries, except Sweden, concerning oxycodone, fentanyl, and methadone ( 21 , 22 ). Morphine had decreasing consumption trend ( 21 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation